2019
DOI: 10.17159/wsa/2019.v45.i3.6733
|View full text |Cite
|
Sign up to set email alerts
|

Membrane surface properties and their effects on real waste oil-in-water emulsion ultrafiltration

Abstract: Membrane surface properties and their effect on the efficiency of ultrafiltration (UF) of real waste oily emulsions was studied. Experiments were performed in cross-flow operation at total recycle condition in a lab-scale system. The ceramic UF membrane in the tubular type module was employed. During the experiments permeate flux was measured. The most important influential factors, such as temperature, TMP, and pH, were considered during the experiments. Zeta potential was measured in order to explain the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The results demonstrated that the final super hydrophobic membrane outperformed hydrophilic ones in terms of self-cleaning. The physical and chemical characteristics of the materials being separated, such as viscosity, charge, stability, and solubility, can be influenced by temperature and pH [ 155 , 156 ]. This could impact on the diffusion rate across the membrane pores.…”
Section: Application Of Coal Fly Ash In Ceramic Membrane For Wastewat...mentioning
confidence: 99%
“…The results demonstrated that the final super hydrophobic membrane outperformed hydrophilic ones in terms of self-cleaning. The physical and chemical characteristics of the materials being separated, such as viscosity, charge, stability, and solubility, can be influenced by temperature and pH [ 155 , 156 ]. This could impact on the diffusion rate across the membrane pores.…”
Section: Application Of Coal Fly Ash In Ceramic Membrane For Wastewat...mentioning
confidence: 99%
“…Our previous investigation of PW treatment with different ceramic MF, UF and NF membranes [22,23,[34][35][36][37] revealed that membrane fouling is a major challenge, causing a significant decline in permeate flux and in some cases reducing oil retention efficiency. Membrane fouling phenomena must therefore be understood in order to control membrane-based filtration processes [57][58][59]. TMP and CFV are critical operational parameters for MF and UF membranes, so we investigated the effect of different TMPs and CFVs on membrane fouling.…”
Section: Characterization Of Membrane Performance-effects Of Operatinmentioning
confidence: 99%
“…Membrane fouling is classed as reversible if it can be controlled by physical or chemical cleaning and irreversible if it accumulates over time and cleaning cannot restore the original membrane performance [64]. The main foulants are organic, colloidal and mineral, which account for 50%, 30% and 20%, of fouling respectively [58]. The purpose of chemical cleaning is to reverse the loss of membrane permeability and restore flux and rejection by removing the foulants described above [54,59].…”
Section: Membrane Chemical-cleaning Proceduresmentioning
confidence: 99%